Orde Subgrup Terkecil yang Memuat Suatu Himpunan dengan 2 Unsur dari Suatu Grup Hingga Siklik - Rasdin Sandria; Jufra Jufra; Norma Muhtar (JOSTECH Journal of Science and Technology, 2023)
Suppose is any group and then the smallest subgroup of containing is the intersection of all subgroups of containing and denoted by . If then , such a subgroup we know as a cyclic group with generator , such that the order of is the same as the order of . In this research, observations were made on the set in order to know the nature of the membership of and the order of for the case of order 2 and further for of order n if G is a cyclic finite group using the effect of Lagrange Theorem.